From PRECIS to precis: retrieval of an expert system for the text analysis and controlled abstracts using PRECIS as a model - Dykstra, Mary (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF